UML profile for goal-oriented modelling - Abid, Muhammad Rizwan (University of Ottawa (Canada), 2008)
The Unified Modeling Language (UML) is a standard for visual modelling. We can design abstract models by using its elements. Although the semantic scope of UML elements is very broad, it does not fully address the needs of some modelling domains, including the modelling of goals and non-functional requirements (NFR). To address this problem, UML allows the customization of its metamodel with an extension mechanism called UML profile. Some work has already been done in the area of UML profiles for NFR and goals. In some cases, the proposed solutions were incorrectly or only partially integrated with UML. Sometimes, the profiles were based on metamodels whose nature and accuracy for this domain were unclear. In other cases, the profiling approaches taken were not well supported by tools, which have led to unsatisfactory solutions. In this thesis, we propose a UML profile for the Goal-oriented Requirement Language (GRL), a goal/NFR notation undergoing standardization at the International Telecommunication Union. Our profile is based on an abstract metamodel of GRL, which has already been successfully tested and implemented in non-UML tools. This profile is also implemented in a UML 2 tool, namely Telelogic G2 4.0, and is well integrated with the rest of UML. Challenges and design decisions for the concrete support of this profile with tools are discussed along the way. The profiling approach used in this thesis is one that has been recommended by modellers and standards developers. Our profile for goal-oriented modelling is also illustrated and validated with several examples.
Keywords: Computer Science.